Dental pulp stem cells (DPSCs), stem cells from human exfoliated deciduous teeth (SHEDSCs), and periodontal ligament stem cells (PDLSCs) isolation, characterization and the effectiveness of allantoin as bioactive molecule for dental regeneration - Ozcinar, Betul Mutlu; Ozukoc, Can; Turkmen, Emrah; Cakir, Rabia (ELSEVIER SCI LTD, 2025)
Introduction: Dental stem cells are valuable tools in regenerative medicine due to their pluripotency and self- renewal properties. This study aimed to investigate the effects of allantoin (Al) on Dental pulp stem cells (DPSCs), stem cells from human exfoliated deciduous teeth (SHEDSCs), and periodontal ligament stem cells (PDLSCs) regarding cytotoxicity, proliferation, wound healing, and osteogenic differentiation. Methods: Human dental stem cells were isolated from three dental tissues using the explant culture method and cultured in DMEM-F12 medium supplemented with 15 % fetal bovine serum (FBS) and antibiotics. The cytotoxicity and proliferation of allantoin were assessed using the XTT cell viability assay at concentrations ranging from 0.25 to 5 mg/mL. Wound healing was evaluated through a scratch assay at 1 mg/mL, and osteogenic differentiation was assessed using Alizarin Red S staining at 0.5 mg/mL and 1 mg/mL. Results: Al exhibited no cytotoxic effects across the tested concentrations. It enhanced cell proliferation, particularly in SHEDSCs at 5 mg/mL. DPSCs also showed significant improvement in wound healing in the scratch assay. At 1 mg/mL, Al inhibited osteogenic differentiation in DPSCs and PDLSCs, as indicated by reduced mineralization. Conclusion: Al shows potential as a non-cytotoxic agent for enhancing the proliferation of dental stem cells, especially SHEDSCs. However, its limited effect on wound healing of SHEDSCs and PDLSCs and inhibition of osteogenic differentiation at higher concentrations suggest that further optimization is required for its application in bone regeneration. Statement of Clinical Relevance: Evaluation of the effects of plant-based therapeutic compounds on various types of dental stem cells may have the potential to increase the success of stem cell-based therapies in clinical applications in regenerative dentistry.
Keywords: Allantoin; Dental pulp stem cells; Stem cells from human exfoliated deciduous; teeth; Periodontal ligament stem cells; Cytotoxicity; Osteogenesis; Dentistry, Oral Surgery & Medicine